PTFIC - Patient Health Tracking through Fog Enabled Internet of Things Network Using Optimized Classifier - Loganathan R., Bibi Ameena, (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The network creates a lot of data, which may be saved and processed by a cloud system, though Internet of Things (IoT) technology reinforced with a fog-enabled cloud computing system to monitor remotely. The data transit between the user and the cloud is processed to generate the communication, internet service, and cloud storage function. To facilitate remote patient monitoring, we suggested PTFIC - patient health tracking over a fog-enabled Internet of Things network utilising an optimised confidence classifier and a fog layer at the gateway. The fog layer oversees patient data validation and transmission by utilising the classifier to analyse significant events by determining the health state.